PATIENT SATISFACTION TOWARDS PHARMACEUTICAL SERVICES AT THE GOVERNMENTAL HEALTH CARE INSTITUTION - Al-Kalbani, Tablib Salim; Iblasi, Abdulkareem S; Al Buriki, Hassan Abdullah; Juanamasta, I Gede (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study aimed to assess patient satisfaction with pharmaceutical services and examine related factors at government medical institutions in Al-Buaraimi Governorate. A cross-sectional design using a standardized self-administered questionnaire was applied. A total of 371 patients were selected through random sampling. The questionnaire covered five domains: sociodemographic characteristics, location, supply, pharmacist’s attitude, and promptness. Data were analyzed using multiple linear regression, Mann-Whitney U, and Kruskal-Wallis tests. The results of the respondents, 55.8% were male, with a mean age of 39.6 years. Overall, 75.27% were satisfied with pharmaceutical services. Highest mean scores were reported for “Pharmacist showed interest in helping me obtain medication” and “Pharmacist showed respect” (4.73), followed by “Received medication within a reasonable time” (4.71) and “Waiting time acceptable considering prescription quantity” (4.69). More than three-quarters (78.7%) used daily medications. Patients visited pharmacies an average of three times annually (SD ±1.372) and received about four items per visit (SD ±1.994). Dispensing took approximately three minutes (SD ±1.213). Four variables showed significant correlation with satisfaction, one showed weak correlation, and one showed no association (p < 0.05). Patient satisfaction with pharmaceutical services was generally high, reflecting the quality of care provided. However, regular audits are recommended to enhance satisfaction and support continuous quality improvement, particularly for national accreditation processes. Strengthening communication between pharmacies and government institutions is also essential to improve services and prevent drug-related issues.